Strategies for Overcoming L1 Interference in English Language Learning: Comparative Insights from Saudi and Pakistani Learners - Mannenkuzhiyan, Shamsudheen; Maqbool, Saira; Sadiq , Uzma; Kurilenko, Viktoria; Al-Hawamdeh, Basem Okleh Salameh; Banu, Sameena (Journal of Education Culture and Society, 2025)
Aim. This research aims to identify the strategies employed by Saudi and Pakistani learners in order to overcome the influence of L1 with English language learning. The study also explores effectiveness of various instructions and techniques used in teaching English language and the cultural attitudes towards second language acquisition in Saudi and Pakistan.Methods. The study purposes questionnaires, interviews, and focus group discussion to reveal different L1 interferences that are phonological, syntactical, lexical, and morphological with 100 learners and 50 instructor participants each from Saudi and Pakistan.Results. The study shows that phonological factors, syntactic aspects, morphological and lexical interferences are major factors that hinder learning a new language and therefore require educational intervention approaches.Conclusions. The study also states best practices to overcome L1 interference, including extra practice, implementation of innovative measures, peer learning, and individualized tutoring etc as the means to address language learning issues. The findings of this research hold great significance to educators and policymakers in devising policies to ensure better English opportunities for Saudi and Pakistani learners.